Combined Immune Therapy for the Treatment of Visceral Leishmaniasis. - Rebecca J Faleiro; Rajiv Kumar; Patrick T Bunn; Neetu Singh; Shashi Bhushan Chauhan; Meru Sheel; Fiona H Amante; Marcela Montes de Oca; Chelsea L Edwards; Susanna S Ng; Shannon E Best; Ashraful Haque; et al. (Public Library of Science (PLoS), 2016)
Chronic disease caused by infections, cancer or autoimmunity can result in profound immune suppression. Immunoregulatory networks are established to prevent tissue damage caused by inflammation. Although these immune checkpoints preserve tissue function, they allow pathogens and tumors to persist, and even expand. Immune checkpoint blockade has recently been successfully employed to treat cancer. This strategy modulates immunoregulatory mechanisms to allow host immune cells to kill or control tumors. However, the utility of this approach for controlling established infections has not been extensively investigated. Here, we examined the potential of modulating glucocorticoid-induced TNF receptor-related protein (GITR) on T cells to improve anti-parasitic immunity in blood and spleen tissue from visceral leishmaniasis (VL) patients infected with Leishmania donovani. We found little effect on parasite growth or parasite-specific IFNγ production. However, this treatment reversed the improved anti-parasitic immunity achieved by IL-10 signaling blockade. Further investigations using an experimental VL model caused by infection of C57BL/6 mice with L. donovani revealed that this negative effect was prominent in the liver, dependent on parasite burden and associated with an accumulation of Th1 cells expressing high levels of KLRG-1. Nevertheless, combined anti-IL-10 and anti-GITR mAb treatment could improve anti-parasitic immunity when used with sub-optimal doses of anti-parasitic drug. However, additional studies with VL patient samples indicated that targeting GITR had no overall benefit over IL-10 signaling blockade alone at improving anti-parasitic immune responses, even with drug treatment cover. These findings identify several important factors that influence the effectiveness of immune modulation, including parasite burden, target tissue and the use of anti-parasitic drug. Critically, these results also highlight potential negative effects of combining different immune modulation strategies.